Excellence in people analytics : how to use workforce data to create business value - Ferrar, Jonathan; Green, David (David Richard) (London ; New York : Kogan Page Limited, 2021)
"Effectively analyzing people data and leveraging the insights from this analysis is what sets the best HR professionals apart. However, knowing what data to collect, how to do this ethically and what questions to ask of the data is crucial for success. Excellence in People Analytics provides HR practitioners with everything they need to know from how to embed the correct infrastructure and technologies for data collection, establish consistent and transparent processes and build a culture of analytics in the HR team. Most importantly, it allows HR professionals to translate their data into tangible actions to improve business performance. Full of practical tools and advice, Excellence in People Analytics enables human resources teams to turn their data into organizational value including increasing profits, improving staff retention and workplace productivity as well as developing individual employee experience. With expert tips on how to present data insights to stakeholders in the rest of the business, assess how new sources of data can impact business growth and build a culture of analytics throughout the HR department. With case studies from global organizations including IBM, Vodafone, Bosch, Disney and AXA, this book is essential reading for all HR professionals needing to unlock the potential in their people data and gain competitive advantage"--
Includes bibliographical references and index.
Catalography
Keywords: Personnel management -- Data processing; Personnel management -- Statistical methods; Personnel management -- Planning